Nonaqueous electrolyte and electrochemical device

JP7643523B2Active Publication Date: 2025-03-11MURATA MFG CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023505172
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-03-11
Filing Date
2022-01-18
Publication Date
2025-03-11
Estimated Expiration
2042-01-18

AI Technical Summary

Benefits of technology

【0011】 本発明の非水系電解液に含まれる金属有機構造体は、二酸化炭素の吸着量がより十分に高い。このため、本発明の非水系電解液を含む電気化学デバイスは、簡易な構造を有しながらも、二酸化炭素ガスの発生による膨れをより十分に防止することができる。詳しくは、本発明の非水系電解液を含む電気化学デバイスにおいて、当該非水系電解液に含まれる金属有機構造体は二酸化炭素の吸着量がより十分に高いため、非水系電解液に混ぜることにより、電気化学デバイスの膨れ防止を簡易な構造で実現できる。より詳しくは、当該金属有機構造体は、電気化学デバイスから発生するガスを吸着でき、安全性および信頼性の高い電気化学デバイスを簡易な構造で実現できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007643523000043
    Figure 0007643523000043
  • Figure 0007643523000044
    Figure 0007643523000044
  • Figure 0007643523000045
    Figure 0007643523000045
Patent Text Reader

Abstract

The present invention provides a non-aqueous electrolyte which includes a metal-organic framework having a sufficiently high adsorption amount of carbon dioxide. The present invention relates to a non-aqueous electrolyte including a metal-organic framework which: contains an azole-based organic molecule that may have a hydrophobic group, and a metal atom; and has a ratio of specific surface area to pore volume of 0.55 Å-1 to 0.71 Å-1.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a non-aqueous electrolyte and an electrochemical device. [Background technology]

[0002] Conventionally, electrochemical devices such as lithium ion secondary batteries and electric double layer capacitors have a structure in which a positive electrode, a negative electrode, a separator, and a non-aqueous electrolyte are enclosed in an exterior body (for example, Non-Patent Document 1). In such electrochemical devices, the non-aqueous electrolyte oxidizes during use, generating gases such as carbon dioxide. This causes an increase in internal pressure, which causes swelling and, in some cases, bursting, and is known to pose safety and reliability problems.

[0003] Therefore, in Patent Document 1, in order to prevent swelling of the lithium ion battery and to increase safety, an attempt is made to place zeolite as an adsorbent in an airtight container separately from the electrolyte. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2015-5496 A [Non-patent literature]

[0005] [Non-Patent Document 1] Ohsaki et al. / Journal of Power Sources 146 (2005) 97-100 Summary of the Invention [Problem to be solved by the invention]

[0006] However, the inventors of the present application have found that the conventional techniques give rise to the following new problems. In the technology of Patent Document 1, since porous materials such as zeolite generally have high water absorption, it is unavoidable to adsorb water during or before the manufacturing process, and when mixed with the electrolyte, the Li salt decomposes and the characteristics deteriorate. Therefore, the Li salt is arranged separately from the electrolyte, but the size of the battery becomes large, the structure becomes complicated, and the cost becomes high.

[0007] Therefore, the inventors of the present application attempted to adsorb carbon dioxide in a non-aqueous electrolyte solution using the metal-organic framework, but further discovered that a new problem arose in that a sufficient amount of carbon dioxide was not adsorbed.

[0008] An object of the present invention is to provide a non-aqueous electrolyte solution containing a metal organic framework that has a sufficiently high adsorption amount of carbon dioxide, and an electrochemical device containing the non-aqueous electrolyte solution.

[0009] Another object of the present invention is to provide an electrochemical device that has a simple structure and yet can more sufficiently prevent swelling due to the generation of carbon dioxide gas. [Means for solving the problem]

[0010] The present invention relates to The composition contains an azole-based organic molecule which may have a hydrophobic group and a metal atom, and has a ratio of a specific surface area to a pore volume of 0.55 Å. -1 More than 0.71 Å -1 The present invention relates to a non-aqueous electrolyte solution containing a metal-organic framework as described below, and an electrochemical device containing the non-aqueous electrolyte solution. Effect of the Invention

[0011] The metal organic framework contained in the nonaqueous electrolyte of the present invention has a sufficiently high adsorption amount of carbon dioxide. Therefore, the electrochemical device containing the nonaqueous electrolyte of the present invention can more sufficiently prevent swelling due to the generation of carbon dioxide gas while having a simple structure. In particular, in the electrochemical device containing the nonaqueous electrolyte of the present invention, the metal organic framework contained in the nonaqueous electrolyte has a sufficiently high adsorption amount of carbon dioxide, so that by mixing it with the nonaqueous electrolyte, it is possible to prevent swelling of the electrochemical device with a simple structure. More specifically, the metal organic framework can adsorb gas generated from the electrochemical device, and a safe and reliable electrochemical device can be realized with a simple structure. [Brief description of the drawings]

[0012] [Figure 1] FIG. 2 is a schematic diagram of a metal-organic framework, which is a schematic diagram showing a crystal structure of the metal-organic framework contained in the nonaqueous electrolyte solution of the present invention. [Diagram 2] FIG. 1 is a schematic cross-sectional view of a secondary battery as an example of an electrochemical device of the present invention. [Diagram 3] FIG. 1 is a schematic cross-sectional view of a capacitor as an example of an electrochemical device of the present invention. [Figure 4] FIG. 2 is a schematic diagram for explaining a method for measuring the amount of adsorption of carbon dioxide measured in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] [Non-aqueous electrolyte] The non-aqueous electrolyte of the present invention is an electrolyte contained in an electrochemical device described below. The non-aqueous electrolyte means an electrolyte in which the medium through which the electrolyte ions move does not contain water, that is, an electrolyte using only an organic solvent as the medium.

[0014] The non-aqueous electrolyte of the present invention contains a specific metal-organic framework (i.e., MOF: Metal-Organic Framework). The metal-organic framework is a crystalline complex formed by bridging metal atoms (particularly metal atom ions) MA with organic molecules OM as ligands, as shown in FIG. 1, and is a porous body based on coordinate bonds between organic molecules and metal atoms (particularly metal atom ions). In this specification, various elements in the drawings are merely shown as schematic and illustrative examples for understanding the present invention, and the appearance and dimensional ratios may differ from the actual ones. The "up-down direction", "left-right direction" and "front-back direction" used directly or indirectly in this specification correspond to the up-down direction, left-right direction and front-back direction in the drawings, respectively, unless otherwise specified. The same sign or symbol indicates the same member or the same meaning except for different shapes, unless otherwise specified.

[0015] In the present invention, the metal organic framework contained in the nonaqueous electrolyte solution is a metal organic framework that contains an azole-based organic molecule which may have a hydrophobic group and a metal atom, and has a ratio of the specific surface area to the pore volume within a specific range.

[0016] The ratio of the specific surface area to the pore volume in the metal organic framework is, in detail, 0.55 Å. -1 More than 0.71 Å -1 From the viewpoint of further increasing the amount of carbon dioxide adsorption in the metal organic framework, it is preferably 0.65 Å or less. -1 More than 0.71 Å -1 Less than or equal to 0.68 Å, more preferably -1 More than 0.71 Å -1The ratio is as follows. When the metal organic framework has such a ratio of specific surface area to pore volume, carbon dioxide can be selectively and more sufficiently adsorbed and captured without inhibition of carbon dioxide adsorption by substances contained in the nonaqueous electrolyte. If the ratio of specific surface area to pore volume is too small, the unevenness of the pores is small, so that when solvent molecules and / or electrolyte salt molecules enter the pores, carbon dioxide cannot be sufficiently adsorbed. If the ratio of specific surface area to pore volume is too large, the unevenness of the pores is large, so that even if solvent molecules and / or electrolyte salt molecules enter the pores, carbon dioxide can be adsorbed, but the adsorbed carbon dioxide is liberated, and carbon dioxide cannot be sufficiently adsorbed and captured.

[0017] The ratio of the specific surface area to the pore volume is one parameter that indicates the roughness of the pores. The larger the ratio of the specific surface area to the pore volume, the larger the roughness of the pores. On the other hand, the smaller the ratio of the specific surface area to the pore volume, the smaller the roughness of the pores.

[0018] In this specification, the ratio of the specific surface area to the pore volume is the specific surface area (m 2 / g) to the pore volume (cm 3 / g) is divided by Å -1 The values ​​obtained by converting into units are used.

[0019] The specific surface area and pore volume are respectively the Connolly surface area (specific surface area) and pore volume calculated from the structural data of the unit crystal of the metal-organic framework with a probe molecular diameter of 3.3 Å. The Connolly surface area is a value calculated by calculating the total area that a sphere with a probe molecular diameter of 3.3 Å can contact with each atom (a sphere with a van der Waals radius) in the metal-organic framework. Similarly, the pore diameter is a value calculated by calculating the volume that a sphere with a probe molecular diameter of 3.3 Å can enter into the gap between each atom (a sphere with a van der Waals radius) in the metal-organic framework. The specific surface area and pore volume can be experimentally measured by the BET method, but the measurement results differ depending on the cleaning conditions and measurement conditions, so they are not accurate. Therefore, by using the above-mentioned method of calculating from the crystal structure, the specific surface area and pore volume of the metal-organic framework can be more accurately calculated.

[0020] The structure of the unit crystal of the metal-organic framework can be detected, for example, by obtaining a crystal diffraction image using a single crystal measurement device manufactured by Rigaku Corporation and analyzing the obtained diffraction image using the analysis software "Yadokari XG2009". The setting conditions of the above measurement device are, for example, as follows: VariMax, a single crystal structure analyzer for extremely small crystals; MoKα radiation (λ=0.71069 Å); Exposure time 4 seconds; d=45mm; 2θ=-20; Temperature=-180℃.

[0021] The specific surface area of ​​the metal organic framework is not particularly limited, and is, for example, 1700 m 2 / g or more 2500m 2 / g or less, and from the viewpoint of further increasing the carbon dioxide adsorption amount in the metal organic framework, preferably 1800 m 2 / g or more 2400m 2 / g or less, more preferably 1950m 2 / g or more 2350m 2 / g or less or 1950m 2 / g or more 2300m2 / g or less, more preferably 2200m 2 / g or more 2350m 2 / g or less or 2200m 2 / g or more 2300m 2 / g or less.

[0022] The pore volume of the metal organic framework is not particularly limited, and may be, for example, 0.20 cm 3 / g or more 0.50cm 3 / g or less, and from the viewpoint of further increasing the amount of carbon dioxide adsorption in the metal organic framework, preferably 0.25 cm 3 / g or more 0.40cm 3 / g or less, more preferably 0.28 cm 3 / g or more 0.35cm 3 / g or less, more preferably 0.31 cm 3 / g or more 0.35cm 3 / g or less.

[0023] The azole-based organic molecule that may have a hydrophobic group may be an azole-based organic molecule that does not have a substituent, or may have only a hydrophobic group as a substituent even if it has a substituent, or may be a mixed molecule thereof. The azole-based organic molecule as an organic molecule that constitutes the metal organic framework does not have a water-absorbing group (or a hydrophilic group) such as an amino group, an imino group, a carboxyl group, a carboxylate group (i.e., a carboxylate group), a hydroxyl group, a ketone group, or an aldehyde group. The metal organic framework containing the azole-based organic molecule that may have a hydrophobic group can have the adsorption property of gas (particularly carbon dioxide) generated from an electrochemical device while having water absorption resistance. Therefore, while more sufficiently preventing the decomposition of the lithium salt, it can adsorb gas (particularly carbon dioxide) generated from the electrochemical device and more sufficiently prevent swelling. In detail, the porosity of the metal organic framework allows the gas (particularly carbon dioxide) generated from the electrochemical device to be adsorbed, thereby obtaining a swelling prevention effect. At the same time, since the metal organic framework is resistant to water absorption, even if it is mixed with an electrolyte, the salt does not decompose, and the swelling prevention effect can be realized with a simple structure. As a result, a safe and reliable electrochemical device can be realized with a simple structure. For example, a porous body such as zeolite easily adsorbs water in addition to carbon dioxide gas. Therefore, if a non-aqueous electrolyte contains a porous body such as zeolite instead of the above-mentioned metal organic framework, the lithium salt decomposes due to a reaction with the adsorbed water, hydrofluoric acid is generated, and components such as electrodes deteriorate. Therefore, the reliability of electrochemical devices such as lithium ion batteries and electric double layer capacitors decreases. In addition, for example, if the organic molecules constituting the metal organic framework have a water-absorbing group (or a hydrophilic group), the organic molecules adsorb water, and thus, as in the case of using a porous body such as zeolite, the lithium salt decomposes due to a reaction with the adsorbed water, and components such as electrodes deteriorate, and the reliability of the electrochemical device decreases.

[0024] The azole-based organic molecule constituting the metal organic framework is one or more organic molecules selected from the group consisting of imidazole, benzimidazole, triazole and purine. From the viewpoint of further increasing the amount of carbon dioxide adsorption in the metal organic framework, it is preferably one or more organic molecules selected from the group consisting of imidazole, benzimidazole and purine, and more preferably one or more (particularly two) organic molecules selected from the group consisting of imidazole and benzimidazole.

[0025] The hydrophobic group that the azole-based organic molecule may have is one or more substituents selected from the group consisting of an alkyl group, a halogen atom, a nitro group, a phenyl group, a pyridyl group, and a cyano group. The azole-based organic molecule constituting the metal organic framework preferably has a hydrophobic group from the viewpoint of further increasing the amount of carbon dioxide adsorbed in the metal organic framework.

[0026] The alkyl group is, for example, an alkyl group having 1 to 5 carbon atoms (particularly, 1 to 3). Specific examples of the alkyl group include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, and an n-pentyl group. Examples of the halogen atom include a fluorine atom, a chlorine atom, and a bromine atom.

[0027] From the viewpoint of further increasing the amount of carbon dioxide adsorption in the metal organic framework, the hydrophobic group is more preferably one or more hydrophobic groups selected from the group consisting of an alkyl group, a halogen atom, and a nitro group, further preferably one or more hydrophobic groups selected from the group consisting of a halogen atom and a nitro group, and particularly preferably a nitro group.

[0028] From the viewpoint of further increasing the amount of carbon dioxide adsorption in the metal organic framework, the azole-based organic molecules constituting the metal organic framework are preferably imidazole-based molecules and / or benzimidazole-based molecules which may have an alkyl group, a halogen atom or a nitro group, and more preferably imidazole-based molecules and / or benzimidazole-based molecules which have an alkyl group, a halogen atom or a nitro group.

[0029] The azole-based organic molecule constituting the metal organic framework is, for example, one or more organic molecules selected from the group consisting of imidazole-based molecules represented by the following general formula (1), benzimidazole-based molecules represented by the following general formula (2), triazole-based molecules represented by the following general formulas (3) and (4), and purine-based molecules represented by the following general formula (5).

[0030] [ka]

[0031] In formula (1), R 1 ~R 3 are each independently a hydrogen atom, an alkyl group, a halogen atom, a nitro group, a phenyl group, a pyridyl group, or a cyano group, and from the viewpoint of further increasing the amount of carbon dioxide adsorbed in the metal organic framework, are preferably a hydrogen atom or a nitro group. 1 and R 3 are each independently a hydrogen atom or a nitro group; R 2 is a hydrogen atom.

[0032] Specific examples of the imidazole-based molecule represented by general formula (1) include the following compounds.

[0033] [Table 1]

[0034] [ka]

[0035] In formula (2), R 11 ~R 15 are each independently a hydrogen atom, an alkyl group, a halogen atom, a nitro group, a phenyl group, a pyridyl group, or a cyano group, and from the viewpoint of further increasing the amount of carbon dioxide adsorbed in the metal organic framework, are preferably a hydrogen atom, an alkyl group, a halogen atom, or a nitro group. 11 , R 13 , R 14 and R 15 is a hydrogen atom, and R 12 is a hydrogen atom, an alkyl group, a halogen atom, or a nitro group.

[0036] Specific examples of the benzimidazole-based molecule represented by the general formula (2) include the following compounds.

[0037] [Table 2]

[0038] [ka]

[0039] In formula (3), R 21 ~R 22 are each independently a hydrogen atom, an alkyl group, a halogen atom, a nitro group, a phenyl group, a pyridyl group, or a cyano group.

[0040] Specific examples of the triazole-based molecule represented by general formula (3) include the following compounds.

[0041] [Table 3]

[0042] [ka]

[0043] In formula (4), R 31 ~R 32 are each independently a hydrogen atom, an alkyl group, a halogen atom, a nitro group, a phenyl group, a pyridyl group, or a cyano group.

[0044] Specific examples of the triazole-based molecule represented by general formula (4) include the following compounds.

[0045] [Table 4]

[0046] [ka]

[0047] In formula (5), R 41 ~R 43 are each independently a hydrogen atom, an alkyl group, a halogen atom, a nitro group, a phenyl group, a pyridyl group, or a cyano group.

[0048] Specific examples of the purine molecule represented by general formula (5) include the following compounds.

[0049] [Table 5]

[0050] The metal atom constituting the metal organic framework is selected from the group consisting of zinc atom, cobalt atom, iron atom, praseodymium atom, cadmium atom, mercury atom, copper atom, indium atom, manganese atom, lithium atom and boron atom, and from the viewpoint of further increasing the carbon dioxide adsorption amount in the metal organic framework, is preferably selected from the group consisting of zinc atom, cobalt atom and iron atom, more preferably selected from the group consisting of zinc atom and cobalt atom, and further preferably zinc atom. The metal atom constituting the metal organic framework may be one or more metal atoms selected from the above group.

[0051] The combination of the azole-based organic molecule and the metal atom in the metal organic framework is not particularly limited, so long as the metal organic framework has the above-mentioned "ratio of specific surface area to pore volume".

[0052] The combination of the azole-based organic molecule and the metal atom in the metal-organic framework may be, for example, the following combination: Combination (C1) = a combination including, as azole-based organic molecules, imidazole-based molecules represented by general formula (1) and benzimidazole-based molecules represented by general formula (2) (preferably only the imidazole-based molecules and the benzimidazole-based molecules), and including, as metal atoms, the above-mentioned metal atoms (preferably zinc atoms, more preferably only zinc atoms); in this combination (C1), from the viewpoint of further increasing the amount of carbon dioxide adsorption in the metal organic framework, a preferred imidazole-based molecule is 2-nitroimidazole, and a preferred benzimidazole-based molecule is one or more selected from the group consisting of 5-nitrobenzimidazole, benzimidazole, 5-chlorobenzimidazole, 5-methylbenzimidazole, and 5-bromobenzimidazole; the molar ratio of the imidazole-based molecule to the benzimidazole-based molecule is not particularly limited, and from the viewpoint of further increasing the amount of carbon dioxide adsorption in the metal organic framework, is preferably 1 / 9 or more and 9 / 1 or less, more preferably 3 / 7 or more and 7 / 3 or less, and even more preferably 4 / 6 or more and 6 / 4 or less: Combination (C2)=A combination containing 4-nitroimidazole (preferably only 4-nitroimidazole) as the azole-based organic molecule and containing the above-mentioned metal atom (preferably a zinc atom, more preferably only a zinc atom) as the metal atom.

[0053] The ratio of organic molecules to metal atoms in the metal organic framework is not particularly limited, but is usually determined by the types of organic molecules and metal atoms that constitute the metal organic framework. For example, an imidazole-based molecule (IM) (e.g., an imidazole-based molecule represented by general formula (1)) and one or more metal atoms (M) selected from the group consisting of zinc atoms, cobalt atoms, iron atoms, copper atoms, manganese atoms, indium atoms, cadmium atoms, lithium atoms, and boron atoms can be used. 1 The metal organic framework containing the compound represented by the formula: M 1 (IM)2; here, although boron atoms are not necessarily classified as metals, they have similar properties to metals in metal-organic frameworks, and are therefore referred to as metal atoms here (hereinafter the same).

[0054] Further, for example, an imidazole-based molecule (IM) (e.g., an imidazole-based molecule represented by general formula (1)) and a benzimidazole-based molecule (BIM) (e.g., a benzimidazole-based molecule represented by general formula (2)) and one or more metal atoms (M) selected from the group consisting of zinc atoms, cobalt atoms, iron atoms, copper atoms, manganese atoms, indium atoms, cadmium atoms, lithium atoms, and boron atoms can be used. 1 The metal organic framework containing the compound represented by the formula: M 1 It can be represented by (IM)(BIM).

[0055] Also, for example, a compound having a benzimidazole-based molecule (BIM) (for example, a benzimidazole-based molecule represented by the general formula (2)) and one or more metal atoms (M) selected from the group consisting of zinc atoms, cobalt atoms, iron atoms, copper atoms, manganese atoms, indium atoms, cadmium atoms, lithium atoms, and boron atoms can be used. 1 The metal organic framework containing the compound represented by the formula: M 1(BIM)2.

[0056] Also, for example, a compound represented by the general formula (3) and / or (4) may be used which is a compound including a triazole-based molecule (TRA) and one or more metal atoms (M) selected from the group consisting of zinc atoms, cobalt atoms, iron atoms, copper atoms, manganese atoms, indium atoms, cadmium atoms, lithium atoms, and boron atoms. 1 The metal organic framework containing the compound represented by the formula: M 1 It can be represented by (TRA)2.

[0057] Also, for example, a purine-based molecule (PUR) (for example, a triazole-based molecule represented by the general formula (5)) and one or more metal atoms (M) selected from the group consisting of zinc atoms, cobalt atoms, iron atoms, copper atoms, manganese atoms, indium atoms, cadmium atoms, lithium atoms, and boron atoms can be used. 1 The metal organic framework containing the compound represented by the formula: M 1 It can be represented by (PUR)2.

[0058] Further, for example, an imidazole-based molecule (IM) (e.g., an imidazole-based molecule represented by general formula (1)) and a benzimidazole-based molecule (BIM) (e.g., a benzimidazole-based molecule represented by general formula (2)) and one or more metal atoms (M) selected from the group consisting of zinc atoms, cobalt atoms, iron atoms, copper atoms, manganese atoms, indium atoms, cadmium atoms, lithium atoms, and boron atoms can be used. 1 The metal organic framework containing the compound represented by the formula: M 1 (IM) x (BIM) y where x+y=2.

[0059] Also, for example, a compound including an imidazole-based molecule (IM) (for example, an imidazole-based molecule represented by general formula (1)) and two or more metal atoms (M) selected from the group consisting of zinc atoms, cobalt atoms, iron atoms, copper atoms, manganese atoms, indium atoms, cadmium atoms, lithium atoms, and boron atoms can be used. 1 and M. 2 The metal organic framework containing the compound represented by the formula: M1 M 2 It can be represented by (IM)4.

[0060] The metal organic framework can be synthesized by mixing a compound containing a predetermined organic molecule and a predetermined metal atom in an aqueous solvent or an organic solvent. In order to promote grain growth, it can be produced by heating to 60 to 150°C. Examples of the compound containing a predetermined metal atom include zinc nitrate, cobalt nitrate, and iron nitrate. Examples of the organic solvent include N,N-diethylformamide, N,N-dimethylformamide, and methanol. The heating time is not particularly limited, and may be, for example, 24 hours or more and 120 hours or less, particularly 72 hours or more and 120 hours or less.

[0061] Metal-organic frameworks are also commercially available. For example, ZIF-8 is available as commercially available ZIF-8 (product name: Basolite Z1200, manufactured by BASF, composition formula: Zn(mIm)2).

[0062] In the present invention, the metal organic framework contained in the nonaqueous electrolyte solution usually has a pore diameter of 1 Å or more and 50 Å or less, and from the viewpoint of further increasing the amount of carbon dioxide adsorption in the metal organic framework, the pore diameter is preferably 1 Å or more and 15 Å or less, particularly preferably 5 Å or more and 12 Å or less, and further preferably 5 Å or more and 10 Å or less.

[0063] The pore size depends on the types (particularly bulkiness and size) of the organic molecules and metal atoms that make up the metal-organic framework. Therefore, the pore size can be adjusted by selecting the types of organic molecules and metal atoms.

[0064] In this specification, the pore size is defined as "the diameter of the largest sphere that can contain each atom in a crystal when it is treated as a hard sphere having a van der Waals radius," and is the pore size when no molecules are contained in the pore. Therefore, the pore size can be calculated from the crystal structure. Such pore sizes are shown in Table 1 of the following document: p(Å) and the values ​​given in the literature can be used: ANH PHAN et al., “Synthesis, Structure, and Carbon Dioxide Capture Properties of Zeolitic Imidazolate Frameworks” (ACCOUNTS OF CHEMICAL RESEARCH 58 67 January 2010 Vol. 43, No. 1)

[0065] The metal organic framework usually has an average particle size of 0.01 μm or more and 1 μm or less in the non-aqueous electrolyte solution, and from the viewpoint of further increasing the amount of carbon dioxide adsorption in the metal organic framework, the average particle size is preferably 0.02 μm or more and 0.5 μm or less, more preferably 0.05 μm or more and 0.2 μm or less.

[0066] The average particle size of the metal-organic framework is the average value of the maximum lengths of 100 arbitrary metal-organic framework particles based on a micrograph.

[0067] The content of the metal organic framework is not particularly limited, and is usually 0.1% by weight or more and 50% by weight or less with respect to the total amount of the nonaqueous electrolyte, and from the viewpoint of further increasing the amount of carbon dioxide adsorption in the metal organic framework, it is preferably 1% by weight or more and 10% by weight or less. The nonaqueous electrolyte may contain two or more types of metal organic frameworks having different organic molecular structures and / or different types of metal atoms, and in that case, the total content thereof may be within the above range.

[0068] The non-aqueous electrolyte usually further contains an organic solvent and an electrolyte salt in addition to the metal-organic framework.

[0069] Examples of the organic solvent include any organic solvent that has been conventionally known in the field of non-aqueous electrolytes for electrochemical devices. Specific examples of the organic solvent include cyclic carbonates of γ-butyrolactone such as propylene carbonate (PC), ethylene carbonate (EC), butylene carbonate (BC), vinylene carbonate (VC), etc.; chain carbonates such as dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dipropyl carbonate (DPC), methyl ethyl carbonate, etc.; tetrahydrofuran, dioxolane, sulfolane, dimethylformamide, dimethylacetamide, N-methyl-2-pyrrolidone, etc. From the viewpoint of further increasing the amount of carbon dioxide adsorption in the metal organic framework, the organic solvent preferably contains carbonates, and more preferably contains only carbonates. The carbonates refer to carbonates including the above-mentioned cyclic carbonates and chain carbonates. When the organic solvent contains carbonates (or only carbonates), the organic solvent contains one or more carbonates selected from the group consisting of cyclic carbonates and chain carbonates. In this case, from the viewpoint of further increasing the amount of carbon dioxide adsorption in the metal-organic framework, the organic solvent preferably contains one or more carbonates (particularly two) selected from the group consisting of cyclic carbonates, and more preferably contains propylene carbonate (PC) and ethylene carbonate (EC).

[0070] The content of the organic solvent is usually 40% by weight or more and 95% by weight or less, relative to the total amount of the nonaqueous electrolyte solution, and from the viewpoint of further increasing the amount of carbon dioxide adsorption in the metal-organic framework, it is preferably 70% by weight or more and 90% by weight or less.

[0071] The electrolyte salt may be any electrolyte salt that has been conventionally known in the field of non-aqueous electrolytes for electrochemical devices. Specific examples of the electrolyte salt include LiPF 6、 LiBF 4、Examples of the electrolyte salt include LiClO4, LiCF3SO3, LiN(CF3SO2)2, LiN(C2F5SO2)2, LiC(CF3SO2)3, and LiC(C2F5SO2)3. From the viewpoint of further increasing the amount of carbon dioxide adsorption in the metal-organic framework, the electrolyte salt preferably contains LiPF6, and more preferably contains only LiPF6.

[0072] The content of the electrolyte salt is usually 5 wt % or more and 25 wt % or less with respect to the total amount of the nonaqueous electrolyte solution, and from the viewpoint of further increasing the amount of carbon dioxide adsorption in the metal organic framework, it is preferably 10 wt % or more and 20 wt % or less.

[0073] The non-aqueous electrolyte may further contain any additives (eg, binders, fillers, etc.) conventionally known in the field of non-aqueous electrolytes for electrochemical devices.

[0074] Examples of the binder include polyacrylonitrile, polyvinylidene fluoride, polytetrafluoroethylene, polyhexafluoropropylene, polyethylene oxide, polypropylene oxide, polyphosphazene, polysiloxane, polyvinyl fluoride (PVF), polychlorotrifluoroethylene (PCTFE), perfluoroalkoxy fluororesin (PFA), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), ethylene-tetrafluoroethylene copolymer (ETFE), ethylene-chlorotrifluoroethylene copolymer (ECTFE), polyvinyl acetate, polyvinyl alcohol, polymethyl methacrylate, polyacrylic acid, polymethacrylic acid, styrene-butadiene rubber, nitrile-butadiene rubber, polystyrene, polycarbonate, polyethylene oxide, and vinyl chloride. The binder may be used alone or in a mixture of two or more. The binder may also be a copolymer composed of two or more monomers constituting the binder. Specific examples of such copolymers include copolymers of vinylidene fluoride and hexafluoropyrene, etc. Among them, polyvinylidene fluoride and copolymers of vinylidene fluoride and hexafluoropyrene are preferred from the viewpoint of electrochemical stability.

[0075] The filler may contain a compound having high heat resistance, such as Al2O3, SiO2, TiO2, or BN (boron nitride).

[0076] The non-aqueous electrolyte solution can be obtained by mixing the metal-organic framework, the organic solvent, the electrolyte salt, and other desired additives. The non-aqueous electrolyte solution can be in the form of a liquid or a gel.

[0077] [Electrochemical Devices] The electrochemical device of the present invention may be any device utilizing an electrochemical reaction, and includes the nonaqueous electrolyte of the present invention. Specific examples of such electrochemical devices include secondary batteries (particularly lithium ion secondary batteries) and capacitors (particularly electric double layer capacitors).

[0078] [Secondary battery] When the electrochemical device of the present invention is a secondary battery, the secondary battery is configured such that, in addition to the non-aqueous electrolyte, a positive electrode, a negative electrode, a separator, and the like are enclosed in an exterior body. In a plan view, a seal part (sealing part) for holding the non-aqueous electrolyte and the like inside the exterior body is usually formed on the periphery of the secondary battery. A plan view refers to a state in which the secondary battery is placed and viewed from directly above in the thickness (height) direction, and is the same as a plan view. The placement refers to, for example, placing the surface of the secondary battery with the largest area as the bottom surface. In this specification, the term "secondary battery" refers to a battery that can be repeatedly charged and discharged. The term "secondary battery" is not excessively limited to its name, and may include, for example, an "electricity storage device".

[0079] The secondary battery 10 of the present invention includes a non-aqueous electrolyte 1, a positive electrode 2, a negative electrode 3, and a separator 4, as shown in FIG. 2, for example, and the positive electrode 2 and the negative electrode 3 are alternately arranged with the separator 4 interposed therebetween. Two external terminals (not shown) are connected to the electrodes (positive electrode or negative electrode) through current collecting leads (not shown), and are consequently led out from the seal portion to the outside. The non-aqueous electrolyte 1 assists the movement of metal ions released from the electrodes (positive electrode and negative electrode). In FIG. 2, the secondary battery 10 has a planar laminated structure in which the positive electrode 2, the negative electrode 3, and the separator 4 arranged between the positive electrode 2 and the negative electrode 3 are laminated in a planar shape, but is not limited to the planar laminated structure. For example, the secondary battery may have a wound structure in which the positive electrode 2, the negative electrode 3, and the separator 4 arranged between the positive electrode 2 and the negative electrode 3 are wound in a roll shape. For example, the secondary battery may have a so-called stack-and-fold structure in which a positive electrode 2, a negative electrode 3, and a separator 4 disposed between the positive electrode 2 and the negative electrode 3 are stacked and then folded. Fig. 2 is a schematic cross-sectional view of a secondary battery as an example of the electrochemical device of the present invention.

[0080] The positive electrode 2 is usually composed of at least a positive electrode layer and a positive electrode current collector (foil), and the positive electrode layer is provided on at least one side of the positive electrode current collector. For example, the positive electrode 2 may have a positive electrode layer provided on both sides of the positive electrode current collector, or may have a positive electrode layer provided on one side of the positive electrode current collector. From the viewpoint of further increasing the capacity of the secondary battery, a preferred positive electrode 2 has a positive electrode layer provided on both sides of the positive electrode current collector. The positive electrode layer contains a positive electrode active material.

[0081] The negative electrode 3 is usually composed of at least a negative electrode layer and a negative electrode current collector (foil), and the negative electrode layer is provided on at least one side of the negative electrode current collector. For example, the negative electrode 3 may have a negative electrode layer provided on both sides of the negative electrode current collector, or may have a negative electrode layer provided on one side of the negative electrode current collector. From the viewpoint of further increasing the capacity of the secondary battery, a preferred negative electrode 3 has a negative electrode layer provided on both sides of the negative electrode current collector. The negative electrode layer contains a negative electrode active material.

[0082] The positive electrode active material contained in the positive electrode layer and the negative electrode active material contained in the negative electrode layer are materials directly involved in the transfer of electrons in the secondary battery, and are the main materials of the positive and negative electrodes that are responsible for charging and discharging, i.e., the battery reaction. More specifically, ions are brought to the non-aqueous electrolyte due to the "positive electrode active material contained in the positive electrode layer" and the "negative electrode active material contained in the negative electrode layer", and these ions move between the positive electrode and the negative electrode to transfer electrons and charge and discharge. Such mediator ions are not particularly limited as long as they can be charged and discharged, and examples thereof include lithium ions or sodium ions (particularly lithium ions). The positive electrode layer and the negative electrode layer may be layers that can particularly absorb and release lithium ions. In other words, the secondary battery may be one in which lithium ions move between the positive electrode and the negative electrode via the non-aqueous electrolyte to charge and discharge the battery. When lithium ions are involved in charging and discharging, the secondary battery according to this embodiment corresponds to a so-called "lithium ion secondary battery".

[0083] The positive electrode active material of the positive electrode layer is preferably made of granular material, and a binder is preferably included in the positive electrode layer to ensure sufficient contact between particles and shape retention. Furthermore, it is also preferable that a conductive assistant is included in the positive electrode layer to facilitate the transfer of electrons that promote the battery reaction. Similarly, the negative electrode active material of the negative electrode layer is preferably made of granular material, and a binder is preferably included in the positive electrode layer to ensure sufficient contact between particles and shape retention, and a conductive assistant may be included in the negative electrode layer to facilitate the transfer of electrons that promote the battery reaction. In this way, since the positive electrode layer and the negative electrode layer are formed by containing multiple components, they can also be called "positive electrode mixture layer" and "negative electrode mixture layer", respectively.

[0084] The positive electrode active material is preferably a material that contributes to the absorption and release of lithium ions. From this perspective, the positive electrode active material is preferably, for example, a lithium-containing composite oxide. More specifically, the positive electrode active material is preferably a lithium transition metal composite oxide containing lithium and at least one transition metal selected from the group consisting of cobalt, nickel, manganese, and iron. That is, in the positive electrode layer of the secondary battery according to this embodiment, such a lithium transition metal composite oxide is preferably contained as the positive electrode active material. For example, the positive electrode active material may be lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium titanate, or a material in which a part of the transition metal is replaced with another metal. Such a positive electrode active material may be contained as a single type, or may be contained in a combination of two or more types. In a more preferred embodiment, the positive electrode active material contained in the positive electrode layer is lithium cobalt oxide.

[0085] The binder that may be included in the positive electrode layer is not particularly limited, but may include at least one selected from the group consisting of polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, vinylidene fluoride-tetrafluoroethylene copolymer, polytetrafluoroethylene, etc. The conductive assistant that may be included in the positive electrode layer is not particularly limited, but may include at least one selected from carbon black such as thermal black, furnace black, channel black, ketjen black, and acetylene black, metal powder such as copper, nickel, aluminum, and silver, and polyphenylene derivatives. In a more preferred embodiment, the binder of the positive electrode layer is polyvinylidene fluoride, and in another more preferred embodiment, the conductive assistant of the positive electrode layer is carbon black. In a further preferred embodiment, the binder and conductive assistant of the positive electrode layer are a combination of polyvinylidene fluoride and carbon black.

[0086] The negative electrode active material is preferably a material that contributes to the absorption and release of lithium ions, and from this viewpoint, the negative electrode active material is preferably, for example, various carbon materials, oxides, lithium alloys, or the like.

[0087] Examples of various carbon materials for the negative electrode active material include graphite (natural graphite, artificial graphite), hard carbon, and diamond-like carbon. In particular, graphite is preferred because of its high electronic conductivity and excellent adhesion to the negative electrode current collector. Examples of oxides for the negative electrode active material include at least one selected from the group consisting of silicon oxide, tin oxide, indium oxide, zinc oxide, and lithium oxide. The lithium alloy for the negative electrode active material may be any metal that can form an alloy with lithium, and may be, for example, a binary, ternary, or higher alloy of lithium and a metal such as Al, Si, Pb, Sn, In, Bi, Ag, Ba, Ca, Hg, Pd, Pt, Te, Zn, or La. It is preferable that such oxides have an amorphous structure. This is because deterioration caused by non-uniformity such as grain boundaries or defects is less likely to occur. In a more preferred embodiment, the negative electrode active material for the negative electrode layer is artificial graphite.

[0088] The binder that may be contained in the negative electrode layer is not particularly limited, but may be at least one selected from the group consisting of styrene butadiene rubber, polyvinylidene fluoride, polyimide resin, and polyamideimide resin. In a more preferred embodiment, the binder contained in the negative electrode layer is styrene butadiene rubber. The conductive assistant that may be contained in the negative electrode layer is not particularly limited, but may be at least one selected from carbon black such as thermal black, furnace black, channel black, ketjen black, and acetylene black, metal powder such as copper, nickel, aluminum, and silver, and polyphenylene derivatives. The negative electrode layer may contain a component resulting from a thickener component (e.g., carboxymethyl cellulose) used during battery production.

[0089] In a more preferred embodiment, the negative electrode active material and binder in the negative electrode layer are a combination of artificial graphite and styrene-butadiene rubber.

[0090] The positive electrode current collector and the negative electrode current collector used for the positive electrode and the negative electrode are members that contribute to collecting and supplying electrons generated in the active material due to the battery reaction. Such a current collector may be a sheet-like metal member and may have a porous or perforated form. For example, the current collector may be a metal foil, a punched metal, a net, an expanded metal, or the like. The positive electrode current collector used for the positive electrode is preferably made of a metal foil containing at least one selected from the group consisting of aluminum, stainless steel, nickel, and the like, and may be, for example, an aluminum foil. On the other hand, the negative electrode current collector used for the negative electrode is preferably made of a metal foil containing at least one selected from the group consisting of copper, stainless steel, nickel, and the like, and may be, for example, a copper foil.

[0091] The separator 4 is a member provided from the viewpoint of preventing short circuit caused by contact between the positive and negative electrodes and retaining a non-aqueous electrolyte. In other words, the separator is a member that allows ions to pass while preventing electronic contact between the positive and negative electrodes. Preferably, the separator is a porous or microporous insulating member, and has a membrane form due to its small thickness. Although merely an example, a microporous membrane made of polyolefin may be used as the separator. In this regard, the microporous membrane used as the separator may contain, for example, only polyethylene (PE) or only polypropylene (PP) as the polyolefin. Furthermore, the separator may be a laminate composed of a "PE microporous membrane" and a "PP microporous membrane".

[0092] The exterior body 5 is preferably a flexible pouch (soft bag body), but may be a hard case (hard housing). When the exterior body 5 is a flexible pouch, the flexible pouch is usually formed from a laminate film, and the peripheral portion is heat-sealed to form a sealed portion. The laminate film is generally a film in which a metal foil and a polymer film are laminated, and specifically, a three-layer structure consisting of an outer layer polymer film / metal foil / inner layer polymer film is exemplified. The outer layer polymer film is for preventing the permeation of moisture and the like and damage to the metal foil due to contact and the like, and polymers such as polyamide and polyester can be suitably used. The metal foil is for preventing the permeation of moisture and gas, and foils such as copper, aluminum, and stainless steel can be suitably used. The inner layer polymer film is for protecting the metal foil from the electrolyte stored inside and for melt-sealing during heat sealing, and polyolefin or acid-modified polyolefin can be suitably used. The thickness of the laminate film is not particularly limited, and for example, 1 μm or more and 1 mm or less are preferable. For example, in the secondary battery 10 shown in FIG. 2, the exterior body 5 is a flexible pouch, and the lower film 5a and the upper film 5b are heat-sealed at their peripheral edges in a plan view.

[0093] When the exterior body 6 is a hard case, the hard case is usually formed from a metal plate, and the peripheral portion is irradiated with a laser to form a seal portion. The metal plate is generally made of a metal material such as aluminum, nickel, iron, copper, or stainless steel. The thickness of the metal plate is not particularly limited, and is preferably, for example, 1 μm or more and 1 mm or less.

[0094] The secondary battery can be manufactured by the following method. First, the positive electrode 2 and the negative electrode 3 are prepared. In detail, the positive electrode 2 can be obtained by mixing the positive electrode active material and the binder together, adding an organic solvent to prepare a slurry, applying the slurry to a positive electrode current collector by any coating method, and drying. The negative electrode 3 can be obtained by mixing the negative electrode active material and the binder together, adding an organic solvent to prepare a slurry, applying the slurry to a negative electrode current collector by any coating method, and drying. The organic solvent contained in the slurry for manufacturing the positive electrode and the negative electrode of the secondary battery is not particularly limited, and for example, organic solvents such as basic solvents such as dimethyl sulfoxide, dimethylformamide, N-methyl-2-pyrrolidone, propylene carbonate, diethyl carbonate, dimethyl carbonate, and γ-butyrolactone, non-aqueous solvents such as acetonitrile, tetrahydrofuran, nitrobenzene, and acetone, and protic solvents such as methanol and ethanol can be used. Next, a positive electrode lead (not shown) is attached to the positive electrode 2, a negative electrode lead (not shown) is attached to the negative electrode 3, and the positive electrode 2 and the negative electrode 3 are laminated via a separator 4 to form a laminated electrode body. If necessary, the laminated electrode body is wound to prepare a wound electrode body, and then a protective tape is applied to the outermost periphery of the wound electrode body. The outer periphery of the outer periphery 5 (5a, 5b) in plan view is bonded to the remaining periphery except for one side of the outer periphery, forming a bag-shaped outer periphery, in which the laminated electrode body or the wound electrode body is housed. After the non-aqueous electrolyte solution 1 is poured into the bag-shaped exterior body, the exterior body is sealed using a heat fusion method or the like. If necessary, a heat treatment may be carried out for thermal polymerization of monomers.

[0095] [Electric double layer capacitor] When the electrochemical device of the present invention is an electric double layer capacitor, the electric double layer capacitor is configured by sealing a positive electrode, a negative electrode, a separator, and the like in addition to the non-aqueous electrolyte solution described above in an exterior body. As shown in FIG. 3, the exterior body 27 has a positive electrode case 27a and a negative electrode case 27b, and the positive electrode case 27a and the negative electrode case 27b are both formed in a disk-like thin plate shape. A positive electrode 22 containing a positive electrode active material (electrode active material) and a conductive agent is disposed in the center of the bottom of the positive electrode case 27a. That is, the positive electrode 22 is formed by forming a mixture containing a positive electrode active material (electrode active material) and a conductive agent into a sheet shape on a positive electrode current collector. Then, a separator 24 formed of a porous sheet or film such as a microporous membrane, woven fabric, or nonwoven fabric is laminated on the positive electrode 22, and a negative electrode 23 is further laminated on the separator 24. That is, in the negative electrode 23, a mixture containing a negative electrode active material (electrode active material) and a conductive agent is formed into a sheet shape on a metallic negative electrode current collector 25, similar to the positive electrode 22. The negative electrode 23 is disposed opposite the positive electrode 22 via a separator 24, and a metallic spring 26 is placed on the negative electrode current collector 25. The nonaqueous electrolyte 21 is filled in the internal space, and the negative electrode case 27b is fixed to the positive electrode case 27a against the biasing force of the metallic spring 26 and sealed via a gasket 28. FIG. 3 is a schematic cross-sectional view showing a coin-type electric double layer capacitor as one embodiment of the electric double layer capacitor according to the present invention.

[0096] In the electric double layer capacitor 20, before a voltage is applied between the positive electrode 22 and the negative electrode 23, the charged particles in the nonaqueous electrolyte 21 are irregularly distributed in the nonaqueous electrolyte 21. On the other hand, when a voltage is applied between the positive electrode 22 and the negative electrode 23, positive ions in the positive electrode 22 and negative ions in the nonaqueous electrolyte 21 are distributed in pairs at the interface between the positive electrode (positive electrode active material) 22 and the nonaqueous electrolyte 21. In addition, negative ions in the negative electrode 23 and positive ions in the nonaqueous electrolyte 21 are distributed in pairs at the interface between the negative electrode (negative electrode active material) 23 and the nonaqueous electrolyte 21. As a result, positive ions and negative ions are distributed in layers at the contact interface with the nonaqueous electrolyte 21 on the positive electrode 22 side, and negative ions and positive ions are distributed in layers at the contact interface with the nonaqueous electrolyte 21 on the negative electrode 23 side, and an electric double layer having a large surface area is formed by these.

[0097] As the positive electrode active material, any material that can be used as a positive electrode active material in the field of electric double layer capacitors can be used. Specific examples of the positive electrode active material include activated carbon.

[0098] As the negative electrode active material, any material that can be used as a negative electrode active material in the field of electric double layer capacitors can be used. Specific examples of the negative electrode active material include carbon.

[0099] The conductive agent that can be contained in the positive electrode and the negative electrode is not particularly limited, and examples thereof include carbonaceous particles such as graphite, carbon black, and acetylene black, carbon fibers such as vapor-grown carbon fibers, carbon nanotubes, and carbon nanohorns, and conductive polymers such as polyaniline, polypyrrole, polythiophene, polyacetylene, and polyacene. The conductive agents can be used alone or in combination of two or more kinds.

[0100] The positive electrode and the negative electrode may each independently contain a binder. As the binder, any binder usable as a binder in the field of the positive electrode and the negative electrode of the electric double layer capacitor can be used. Specific examples of such binders include, for example, polyethylene, polypropylene, polyvinylidene fluoride, polyhexafluoropropylene, polytetrafluoroethylene, polyethylene oxide, carboxymethyl cellulose, styrene butadiene copolymer, polymethyl acrylate, etc. The binder can be used alone or in combination of two or more kinds.

[0101] Separator 24 may be selected from the same range as separator 4 of the secondary battery.

[0102] The electric double layer capacitor can be manufactured by the following method. First, the positive electrode 22 and the negative electrode 23 are prepared. In detail, the positive electrode 22 can be obtained by mixing the positive electrode active material, the conductive agent, the binder, etc. together, adding an organic solvent to prepare a slurry, applying the slurry to a positive electrode current collector by any coating method, and drying. The negative electrode 23 can be obtained by mixing the negative electrode active material, the conductive agent, the binder, etc. together, adding an organic solvent to prepare a slurry, applying the slurry to a negative electrode current collector by any coating method, and drying. The organic solvent contained in the slurry for producing the positive electrode and the negative electrode of the electric double layer capacitor is not particularly limited, and for example, an organic solvent similar to the organic solvent contained in the slurry for producing the positive electrode and the negative electrode of the secondary battery may be used. Next, the positive electrode 22 is impregnated with the nonaqueous electrolyte solution 21, and the negative electrode 23 and the negative electrode current collector 25 are arranged so as to face the positive electrode 22 via the separator 24 impregnated with the nonaqueous electrolyte solution 21, and then the nonaqueous electrolyte solution 21 is poured into the internal space. Then, a metal spring 26 is seated on the negative electrode current collector 25, a gasket 28 is placed on the periphery, and the negative electrode case 27b is fixed to the positive electrode case 27a by a crimping machine or the like to seal the exterior, thereby producing a coin-type electric double layer capacitor.

[0103] Although the electric double layer capacitor of this embodiment has been described as a coin-type electric double layer capacitor, the shape is not particularly limited. The electric double layer capacitor may be cylindrical, rectangular, sheet-shaped, etc. Furthermore, the exterior body 27 is also not particularly limited, and a metal case, molded resin, aluminum laminate film, etc. may be used. EXAMPLES

[0104] [Production of Metal-Organic Frameworks] Example 1 The metal-organic framework ZIF-78 was synthesized by the following method. 60mL of N,N-dimethylformamide solution containing 0.2M of both 2-nitroimidazole and 5-nitrobenzimidazole as organic molecules and 20mL of N,N-dimethylformamide solution containing 0.2M of zinc nitrate were mixed and heated at 140℃ for 96 hours in a stainless jacket to obtain a powder. The powder was then washed three times with N,N-dimethylformamide solution, centrifuged, and dried to obtain ZIF-78. ZIF-78 is composed of zinc atoms, 2-nitroimidazole, and 5-nitrobenzodazole, and has the formula Zn(2nIm)(5nbIm), a specific surface area / pore volume ratio of 0.67, a pore diameter of 7.1 Å, and an average particle size of 0.1 μm.

[0105] Example 2 ZIF-68 was synthesized by the same method as that for ZIF-78, except that an N,N-dimethylformamide solution containing 0.2 M of both 2-nitroimidazole and benzimidazole was used. ZIF-68 is composed of zinc atoms, 2-nitroimidazole, and benzimidazole, and has the formula Zn(2nIm)(bIm), with a specific surface area / pore volume ratio of 0.57. The pore diameter was 10.3 Å, and the average particle size was 0.1 μm.

[0106] Example 3 ZIF-69 was synthesized by the same method as that for ZIF-78, except that an N,N-dimethylformamide solution containing 0.2 M of both 2-nitroimidazole and 5-chlorobenzimidazole was used. ZIF-69 is composed of zinc atoms, 2-nitroimidazole, and 5-chlorobenzimidazole, and has the formula Zn(2nIm)(5cbIm), with a specific surface area / pore volume ratio of 0.62. The pore diameter was 7.8 Å, and the average particle size was 0.1 μm.

[0107] Example 4 ZIF-79 was synthesized by the same method as that for ZIF-78, except that an N,N-dimethylformamide solution containing 0.2 M of both 2-nitroimidazole and 5-methylbenzimidazole was used. ZIF-79 is composed of zinc atoms, 2-nitroimidazole, and 5-methylbenzimidazole, and has the formula Zn(2nIm)(5mbIm), with a specific surface area / pore volume ratio of 0.63. The pore diameter was 7.5 Å, and the average particle size was 0.1 μm.

[0108] Example 5 ZIF-81 was synthesized by the same method as that for ZIF-78, except that an N,N-dimethylformamide solution containing 0.2 M of both 2-nitroimidazole and 5-bromobenzimidazole was used. ZIF-81 is composed of zinc atoms, 2-nitroimidazole, and 5-bromobenzimidazole, and has the formula Zn(2nIm)(5bbIm), with a specific surface area / pore volume ratio of 0.62. The pore diameter was 7.4 Å, and the average particle size was 0.1 μm.

[0109] Example 6 Zn(4nIm)2 was synthesized by the same method as that for ZIF-78, except that a solution of 0.4 M 4-nitroimidazole in N,N-dimethylformamide was used. Zn(4nIm)2 is composed of zinc atoms and 4-nitroimidazole, and is represented by the formula Zn(4nIm)2. The specific surface area / pore volume ratio was 0.70. The pore diameter was 6.0 Å, and the average particle size was 0.1 μm.

[0110] Comparative Example 1 ZIF-8 was synthesized by the same method as that for ZIF-78, except that an N,N-dimethylformamide solution containing 0.4 M of 2-methylimidazole was used. ZIF-8 consists of zinc atoms and 2-methylimidazole, and is represented by the formula Zn(2mIm)2. The specific surface area / pore volume ratio was 0.50. The pore diameter was 11.6 Å, and the average particle size was 0.1 μm.

[0111] Comparative Example 2 ZIF-77 was synthesized by the same method as that for ZIF-78, except that an N,N-dimethylformamide solution containing 0.4 M of 2-nitroimidazole was used. ZIF-77 consists of zinc atoms and 2-nitroimidazole, and has the formula Zn(2nIm)2, with a specific surface area / pore volume ratio of 0.74. The pore diameter was 3.6 Å, and the average particle size was 0.1 μm.

[0112] Comparative Example 3 ZIF-4 was synthesized by the same method as that for ZIF-78, except that an N,N-dimethylformamide solution containing 0.4 M imidazole was used. ZIF-4 is composed of zinc atoms and imidazole, and is represented by the formula Zn(Im)2. The specific surface area / pore volume ratio was 1.02. The pore diameter was 2.1, and the average particle diameter was 0.1 μm.

[0113] Comparative Example 4 ZIF-7 was synthesized by the same method as that for ZIF-78, except that an N,N-dimethylformamide solution containing 0.4 M benzimidazole was used. ZIF-7 consists of zinc atoms and benzimidazole, and is represented by the formula Zn(bIm)2. The specific surface area / pore volume ratio was 1.02. The pore diameter was 4.3 Å, and the average particle size was 0.1 μm.

[0114] (Metal-organic framework structure and specific surface area / pore volume ratio) A crystal diffraction image was obtained using a single crystal measurement device manufactured by Rigaku Corporation (VariMax single crystal structure analysis device for extremely small crystals, MoKα radiation (λ=0.71069Å), irradiation time 4 seconds, d=45 mm, 2θ=-20, temperature=-180℃), and the obtained diffraction image was analyzed using the analysis software "Yadokari XG2009" to obtain the structure of the unit crystal. From the obtained unit crystal structure, the Connolly surface area (specific surface area) and the pore volume were calculated at a probe molecular diameter of 3.3 Å, and the ratio of the specific surface area to the pore volume was calculated. For example, in the case of ZIF-78 in Example 1, the specific surface area was 2004 m 2 / g, pore volume 0.30 cm 3 The specific surface area / pore volume ratio was 0.67. The same calculations were performed for Examples 2 to 6, and the results are shown in Table 6. Here, the specific surface area and pore volume can be experimentally measured using the BET method, but the measurement results vary depending on the cleaning conditions and measurement conditions, making them inaccurate. Therefore, the CO2 adsorption selectivity can be evaluated more accurately by calculating them from the crystal structure as described above. In the formula, the following abbreviations are used: 2nIm: 2-nitroimidazole; bIm: benzimidazole; 4nIm: 4-nitroimidazole; 5mbIm: 5-methylbenzimidazole; 5cbIm: 5-chlorobenzimidazole; 5bbIm: 5-bromobenzimidazole; 5nbIm: 5-nitrobenzimidazole.

[0115] (Prediction of CO2 adsorption amount) The amount of CO2 adsorption in a non-aqueous electrolyte containing a metal-organic framework can be predicted by the Grand Canonical Monte Carlo method (GCMC method). For the metal-organic framework, calculations were performed for the amount of gas adsorption (equilibrium state) of CO2: 100 kPa, ethylene carbonate: 10,000 kPa, and propylene carbonate: 10,000 kPa at a temperature condition of 298 K. The software used was Materials Studio Sorption (Dassault Systemes), and calculations were performed using the Metropolitan method using the attached COMPASS II force field. In detail, calculations were performed using the structures and conditions shown in Table 7 below, and under the simulation conditions shown in Tables 8-1 to 8-25 below.

[0116] The predicted values ​​and the measured values ​​described below were evaluated according to the following criteria. ◎◎: 120 mL / g or less gas adsorption amount (best); ◎: 100mL / g≦gas adsorption amount<120mL / g (excellent); ○: 60 mL / g or less gas adsorption amount < 100 mL / g (good); △: 50mL / g≦Gas adsorption amount<60mL / g (no practical problem) ×: Gas adsorption amount <50 mL / g (problematic in practical use). The results are shown in Table 6.

[0117] (Measurement of CO2 adsorption amount) The amount of CO2 adsorption into the non-aqueous electrolyte solution containing the metal-organic framework was measured according to the method shown in Figure 4. The details are as follows. (1) An exterior body 51 for measurement was prepared. The exterior body 51 was obtained by heat-sealing the three outer peripheral edges and the central portion 60 of two rectangular laminate films in a plan view. A gas adsorption chamber 51a and a gas injection chamber 51b were provided by forming a sealed portion of the central portion 60. When forming the sealed portion of the central portion 60, a non-sealed portion 61 was provided for moving CO2 gas as described below. An injection port 52 for injecting gas was provided in the gas injection chamber 51b. (2) The exterior body 51 was folded back at the heat-sealed portion of the center portion 60, and 2 mL of a non-aqueous electrolyte solution containing 5 wt% of the metal-organic framework shown in each Example / Comparative Example, 1 mol / kg of LiPF6, and composed of ethylene carbonate and propylene carbonate in a ratio of 1:1 was injected from the opening of the gas adsorption chamber 51a. The metal-organic framework was then left for one week at 60°C so that the solvent would permeate the metal-organic framework. Note that clips 53 were used at the bottoms of the gas adsorption chamber 51a and the gas injection chamber 51b to restrict the mutual movement of the contents of both chambers. The total content of ethylene carbonate and propylene carbonate was 85 wt% with respect to the total amount of the non-aqueous electrolyte. The content of LiPF6 was 15 wt% with respect to the total amount of the non-aqueous electrolyte. (3) The opening of gas adsorption chamber 51a was heat sealed and weighed. The weight Ws of the test specimen alone was calculated from the weight including clip 53, gas inlet 52, and test specimen (i.e., the electrolyte liquid-encapsulating outer casing) and the weight of clip 53 and gas inlet 52. (4) CO 2 gas (1.5 mL) was injected into the gas injection chamber 51b through the gas injection port 52. (5) The vicinity 55 of the gas injection port 52 in the gas injection chamber 51b is heat sealed to prevent gas leakage. (6) According to Archimedes' principle, the volume (V1) of the test specimen equipped with the clip 53 was measured. (7) The clip 53 was removed, and the CO2 gas was moved from the gas injection chamber 51b to the gas adsorption chamber 51a, and the CO2 gas was sufficiently adsorbed. (8) After the adsorption of CO2 gas, the volume (V2) of the test specimen equipped with clip 53 was measured according to Archimedes' principle. The gas adsorption amount was calculated from the values ​​measured by the above method according to the following formula. This value was evaluated according to the same criteria as the evaluation criteria for the predicted value. The results are shown in Table 6. Gas adsorption amount (mL / g) = (V1-V2) / Ws

[0118] [Table 6]

[0119] The predicted values ​​by the GCMC method correspond and match extremely well with the measured values. That is, the predicted values ​​and the measured values ​​are the same. From this, it can be confirmed that the metal organic frameworks of Examples 1 to 6 have a more sufficient CO2 adsorption performance in the electrolyte compared to the metal organic frameworks of Comparative Examples 1 to 4. That is, the ratio of the specific surface area to the pore volume is 0.55 Å or less. -1 More than 0.71 Å -1 Less than or equal to 0.65 Å -1 More than 0.71 Å -1 Less than or equal to 0.68 Å, more preferably -1 More than 0.71 Å -1 By satisfying the above condition, the amount of CO2 adsorption in the electrolyte can be made sufficiently large.

[0120] When a secondary battery was produced using the nonaqueous electrolyte solution containing the metal organic framework obtained in each Example, the secondary battery had the inherent function of a secondary battery.

[0121] When an electric double layer capacitor was produced using the nonaqueous electrolyte solution containing the metal organic framework obtained in each Example, the electric double layer capacitor had the inherent function of an electric double layer capacitor.

[0122] [Table 7]

[0123] In Table 7, the RCSR topology is based on the following literature (1). (1)O'Keeffe, M.; Peskov, MA; Ramsen, SJ; Yaghi, OM The Reticular Chemistry Structure Resource (RCSR) Database of, and Symbols for, Crystal Nets. Acc. Chem. Res. 2008, 41, 1782-1789.

[0124] [Table 8-1]

[0125]

Table 8-2

[0126]

Table 8-3

[0127]

Table 8-4

[0128]

Table 8-5

[0129]

Table 8-6

[0130]

Table 8-7

[0131]

Table 8-8

[0132]

Table 8-9

[0133]

Table 8-10

[0134]

Table 8-11

[0135]

Table 8-12

[0136]

Table 8-13

[0137]

Table 8-14

[0138]

Table 8-15

[0139]

Table 8-16

[0140]

Table 8-17

[0141]

Table 8-18

[0142]

Table 8-19

[0143]

Table 8-20

[0144]

Table 8-21

[0145] [Table 8-22]

[0146] [Table 8-23]

[0147] [Table 8-24]

[0148] [Table 8-25] [Industrial Applicability]

[0149] The electrochemical device including the metal organic framework according to the present invention can be used in various fields where the use of batteries or storage of electricity is expected. By way of example only, the electrochemical device according to the present invention, particularly the secondary battery and the electric double layer capacitor, can be used in the field of electronics packaging. The secondary battery and the electric double layer capacitor according to an embodiment of the present invention can also be used in the electric / information / communication field where mobile devices and the like are used (e.g., electric / electronic device fields including small electronic devices such as mobile phones, smartphones, notebook computers, digital cameras, activity meters, arm computers, electronic paper, wearable devices, RFID tags, card-type electronic money, and smart watches, or the mobile device field), household and small industrial applications (e.g., power tools, golf carts, household, nursing care, and industrial robots), large industrial applications (e.g., forklifts, elevators, and port cranes), transportation systems (e.g., hybrid cars, electric cars, buses, trains, electrically assisted bicycles, and electric motorcycles), power system applications (e.g., various power generation, road conditioners, smart grids, and general household installation-type power storage systems), medical applications (medical devices such as earphones and hearing aids), pharmaceutical applications (medical management systems), IoT, and space and deep sea applications (e.g., space probes, submersible research vessels, and the like). [Explanation of symbols]

[0150] 1: Non-aqueous electrolyte 2: Positive electrode 3: Negative electrode 4: Separator 5: Exterior body 10: Secondary battery 20: Electric double layer capacitor 21: Non-aqueous electrolyte 22: Positive electrode 23: Negative electrode 24: Separator 27: Exterior body

Claims

1. The pore volume ratio of the azole-based organic molecule having a hydrophobic group and a metal atom is 0.65 Å. -1 More than 0.71 Å -1 A non-aqueous electrolyte solution, which is a mixture of a metal-organic framework, an organic solvent, and an electrolyte salt, which is:

2. The specific surface area is 1700 m 2 / g or more 2500m 2 The nonaqueous electrolyte according to claim 1, wherein the pH is 1.0 or less.

3. The specific surface area is 1950 m 2 / g or more 2300m 2 The nonaqueous electrolyte according to claim 1, wherein the pH is 1.0 or less.

4. The pore volume ratio of the azole-based organic molecule having a hydrophobic group and a metal atom is 0.55 Å. -1 More than 0.71 Å -1 a mixture of a metal organic framework having a specific surface area of ​​1950 m or less, an organic solvent and an electrolyte salt, 2 / g or more 2300m 2 / g or less.

5. The pore volume is 0.20 cm 3 / g or more 0.50cm 3 The nonaqueous electrolyte solution according to any one of claims 1 to 4, wherein the pH is 1.0 or less.

6. The pore volume is 0.28 cm 3 / g or more 0.35cm 3 The nonaqueous electrolyte solution according to any one of claims 1 to 4, wherein the pH is 1.0 or less.

7. The nonaqueous electrolyte solution according to any one of claims 1 to 6, wherein the azole-based organic molecule is one or more organic molecules selected from the group consisting of imidazole, benzimidazole, triazole, and purine.

8. The nonaqueous electrolyte solution according to any one of claims 1 to 7, wherein the hydrophobic group is one or more substituents selected from the group consisting of an alkyl group, a halogen atom, a nitro group, a phenyl group, a pyridyl group, and a cyano group.

9. The nonaqueous electrolyte solution according to any one of claims 1 to 8, wherein the metal atom is one or more metal atoms selected from the group consisting of a zinc atom, a cobalt atom, an iron atom, a praseodymium atom, a cadmium atom, a mercury atom, a copper atom, an indium atom, a manganese atom, a lithium atom, and a boron atom.

10. The azole-based organic molecule is one or more organic molecules selected from the group consisting of imidazole-based molecules represented by the following general formula (1), benzimidazole-based molecules represented by the following general formula (2), triazole-based molecules represented by the following general formulas (3) and (4), and purine-based molecules represented by the following general formula (5): 【Chemistry 1】 【Chemistry 2】 【Chemistry 3】 【Chemistry 4】 【Chemistry 5】 (In formulas (1) to (5), R 1 ~R 3 , R 11 ~R 15 , R 21 ~R 22 , R 31 ~R 32 , and R 41 ~R 43 are each independently a hydrogen atom, an alkyl group, a halogen atom, a nitro group, a phenyl group, a pyridyl group, or a cyano group).

11. The metal organic framework includes, as the azole-based organic molecule, the imidazole-based molecule and the benzimidazole-based molecule, or includes 4-nitroimidazole, and includes, as the metal atom, a zinc atom. The nonaqueous electrolyte solution according to claim 10.

12. The nonaqueous electrolyte solution according to any one of claims 1 to 11, wherein the nonaqueous electrolyte solution contains the metal organic framework in an amount of 0.1 wt% or more and 50 wt% or less with respect to a total amount of the nonaqueous electrolyte solution.

13. The nonaqueous electrolyte solution according to any one of claims 1 to 12, further comprising an organic solvent and an electrolyte salt.

14. The nonaqueous electrolyte solution according to claim 13 , wherein the organic solvent comprises a carbonate.

15. The nonaqueous electrolyte solution according to any one of claims 1 to 14, which is contained in an electrochemical device.

16. The nonaqueous electrolyte according to claim 15, wherein the electrochemical device is a lithium ion secondary battery or an electric double layer capacitor.

17. The nonaqueous electrolyte solution according to claim 1, wherein the metal organic framework contains 4-nitroimidazole as the azole-based organic molecule.

18. The nonaqueous electrolyte solution according to claim 1, wherein the metal organic framework contains 4-nitroimidazole as the azole-based organic molecule and a zinc atom as the metal atom.

19. An electrochemical device comprising the nonaqueous electrolyte solution according to any one of claims 1 to 18.

20. 20. The electrochemical device of claim 19, wherein the electrochemical device is a lithium ion secondary battery or an electric double layer capacitor.

21. the electrochemical device is a lithium ion secondary battery; The lithium ion secondary battery further includes a positive electrode and a negative electrode, 21. The electrochemical device according to claim 19, wherein the positive electrode and the negative electrode have a layer capable of absorbing and releasing lithium ions.

Citation Information

Patent Citations

  • PEO-coated activated nanoparticle composite solid electrolyte and preparation method thereof

    CN110518279A

  • Additive for low-temperature lithium ion battery, electrolyte using additive and lithium ion battery

    CN111293359A

  • Lithium secondary battery

    JP2006260889A

  • Lithium ion battery, and electronic device using the same

    JP2015005496A